Exaggerated Exercise Blood Pressure as a Marker of Baroreflex Dysfunction in Normotensive Metabolic Syndrome Patients - Dutra-Marques, Akothirene C.; Rodrigues, Sara; Cepeda, Felipe X.; Toschi-Dias, Edgar; Rondon, Eduardo; Carvalho, Jefferson C.; Alves, Maria Janieire N. N.; Braga, Ana Maria F. W.; Rondon, Maria Urbana P. B.; Trombetta, Ivani C. (Frontiers in Neuroscience, 2021)
Introduction: Exaggerated blood pressure response to exercise (EEBP = SBP≥190 mmHg for women and ≥210 mmHg for men) during cardiopulmonary exercise test (CPET) is a predictor of cardiovascular risk. Sympathetic hyperactivation and decreased baroreflex sensitivity (BRS) seem to be involved in the progression of metabolic syndrome (MetS) to cardiovascular disease. Objective: To test the hypotheses: (1) MetS patients within normal clinical BP may present EEBP response to maximal exercise; and (2) Increased muscle sympathetic nerve activity (MSNA) and reduced BRS are associated with this impairment. Methods: We selected MetS (ATP III) patients with normal BP (MetS_NT, n=27, 59.3% males, 46.1±7.2 years) and a control group without MetS (C, n=19, 48.4±7.4 years). We evaluated BRS for increases (BRS+) and decreases (BRS-) in spontaneous BP and HR fluctuations, MSNA (microneurography), BP from Ambulatory Blood Pressure Monitoring (ABPM), and auscultatory BP during CPET. Results: MetS_NT had higher BMI and impairment in all MetS risk factors when compared to C group. MetS_NT had higher peak SBP (195±17 vs. 177±24 mmHg, P=0.007) and DBP (91±11 vs. 79±10 mmHg, P=0.001) during CPET than the C. Additionally, we found that MetS patients with normal BP had lower spontaneous BRS- (9.6±3.3 vs. 12.2±4.9 ms/mmHg, P=0.044) and higher levels of MSNA (29±6 vs. 18±4 bursts/min, P<0.001) compared to C. Interestingly, 10 out of 27 MetS_NT (37%) showed EEBP (MetS_NT+), whereas 2 out of 19 C (10.5%) presented (P=0.044). The subgroup of MetS_NT with EEBP (MetS_NT+, n=10) had similar MSNA (P=0.437), but lower BRS+ (P=0.039) and BRS- (P=0.039) compared with the subgroup without EEBP (MetS_NT-, n=17). Either office BP or BP from ABPM were similar between subgroups MetS_NT+ and MetS_NT-, regardless EEBP response. In MetS_NT+ subgroup there was an association of peak SBP with BRS- (r=-0.70; P=0.02), triglycerides with peak SBP during CPET (R=0.66; P=0.039) and of triglycerides with BRS- (R=0.71; P=0.022). Conclusion: Normotensive MetS patients already presented higher peak systolic and diastolic BP during maximal exercise, in addition to sympathetic hyperactivation and decreased baroreflex sensitivity. The EEBP in MetS_NT with apparent well controlled BP may indicate a potential depressed neural baroreflex function, predisposing these patients to increased cardiovascular risk.